PENEGAKAN SYARIAT ISLAM DALAM PERSPEKTIF HAM INTERNASIONAL DAN KONSTITUSI - M. Asfar Marzuki (Jurnal Masyarakat dan Budaya, 2006)
This study reveals that the implementation of Islamic syariat has fundamentally changed its view from political issue to basic human rights. The existing of Indonesian government can not eventually stop the implementation of syariat Islam taking place in Indonesia. The International Covenant on Civics and Political Rights (ICCPR) 1966 and the International Covenant on Economic, Social and Cultural Rights (ICESCR) 1996 and also the 1945 Indonesian Constitution have shown to concern in protecting religious implementation. The implementation of Islamic Syariat Law in Aceh, Banten and South Sulawesi Provinces has given a significant evidence. The notion of the freedom expression and freedom of religion based on international and national laws make Indonesian government has dramatically changed its attitude to be more democratic and tolerant. Keywords: Syariat Islam, Hak Asasi Manusia, Konstitusi